Interannual temperature rise leads to more uniform phenological matching between invasive Stellera chamaejasme and pollinators across elevations - Miao, Chenxin; Du, Jun; Wang, Wen; Wu, Juanjuan; Wu, Longqing; Zhang, Kehai; Ma, Xuee (Frontiers in Plant Science, 2024)
Exploring how environmental changes induce alterations in the phenology matching between plants and pollinators is significant for predicting species’ reproductive output and population dynamics. Our study focused on the invasive poisonous weed Stellera chamaejasme, widely distributed in the Qilian Mountains, China. By continuously monitoring its flowering phenology and flower visitors’ activities across different elevational ranges, we compared phenological matching patterns between S. chamaejasme and its potential pollinators across years with varying environmental temperatures. We found that S. chamaejasme, a typical early-flowering alpine species, begins its flowering in early June. Despite variations in the composition of flower-visiting insects across elevations and years, it maintained stable interactions with four major groups: Meloidae, Tachinidae, Scarabaeidae, and Noctuidae. Phenological mismatches between the peak flowering period of S. chamaejasme and the peak abundance of major potential pollinators were generally observed across its range, with higher phenological matching at higher elevations. This enhanced matching at higher elevations may drive the rapid invasion of S. chamaejasme in these areas. In the year with higher ambient temperature, phenological matching increased across its range, and its elevational sensitivity decreased, potentially contributing to its ongoing expansion in different elevations. The results of our study advance a new insight into the population expansion of invasive species in mountain ecosystems.